Cytotoxic Activity of Amaryllidaceae Plants against Cancer Cells: Biotechnological, In Vitro, and In Silico Approaches (2023)
Cancer is a major cause of death and an impediment to increasing life expectancy worldwide. With the aim of finding new molecules for chemotherapeutic treatment of epidemiological relevance, ten alkaloid fractions from Amaryllidaceae species were tested against six cancer cell lines (AGS, BT-549, HEC-1B, MCF-7, MDA-MB 231, and PC3) with HaCat as a control cell line. Some species determined as critically endangered with minimal availability were propagated using in vitro plant tissue culture techniques. Molecular docking studies were carried out to illustrate binding orientations of the 30 Amaryllidaceae alkaloids identified in the active site of some molecular targets involved with anti-cancer activity for potential anti-cancer drugs. In gastric cancer cell line AGS, the best results (lower cell viability percentages) were obtained for Crinum jagus (48.06 ± 3.35%) and Eucharis bonplandii (45.79 ± 3.05%) at 30 µg/mL. The research focused on evaluating the identified alkaloids on the Bcl-2 protein family (Mcl-1 and Bcl-xL) and HK2, where the in vitro, in silico and statistical results suggest that powelline and buphanidrine alkaloids could present cytotoxic activity. Finally, combining experimental and theoretical assays allowed us to identify and characterize potentially useful alkaloids for cancer treatment.